2012
DOI: 10.4081/hr.2012.e8
|View full text |Cite
|
Sign up to set email alerts
|

Hematological Profile of Sickle Cell Disease from South Gujarat, India

Abstract: The aim of this study was to determine hematological profile of sickle cell disease (SCD) from Surat, South Gujarat, India. This prospective cross-sectional study was conducted in the Department of Pediatrics and Sickle Cell Anemia Laboratory, Faculty of Pathology, Government Medical College, Surat, India, between July 2009 and December 2010. Patients included in this study were in their steady state for a long period of time without any symptoms related to SCD or other diseases which could affect the hematolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
15
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 11 publications
10
15
0
Order By: Relevance
“…[4] Our study shows decreased levels of RBC count , MCV , Hematocrit (PCV) which correlates with the study done by Kar et al (1986). [5] Balgir et al (2000) [3] in his study showed lower MCV levels (60-113 fl).Rao et al (2012) [6] showed lowering of above parameters in their respective studies, thus supporting our study.…”
Section: Discussionsupporting
confidence: 85%
“…[4] Our study shows decreased levels of RBC count , MCV , Hematocrit (PCV) which correlates with the study done by Kar et al (1986). [5] Balgir et al (2000) [3] in his study showed lower MCV levels (60-113 fl).Rao et al (2012) [6] showed lowering of above parameters in their respective studies, thus supporting our study.…”
Section: Discussionsupporting
confidence: 85%
“…[8] Observations of decreased MCV are also there, justified by concurrent iron deficiency. [15][16] Increased MCV has also been reported. [13] This may be owing to increased requirement of folate due to hemolysis and concurrent folate deficiency.…”
Section: Discussionmentioning
confidence: 88%
“…23,24 Lower MCH count was distinct for the children with SCD, which is substantiated by findings from other parts of the world. 25,26 A lower MCH is possibly due to the hemolytic tendencies conferred by the sickling of fragile RBCs during crisis without a concomitant rapid replacement with fully formed RBCs. However, we observed no distinct hematological indices among the children with typhoid, diarrhea, and malariatyphoid co-infection.…”
Section: Discussionmentioning
confidence: 99%